Facilitating students’ creativity in an EFL writing classroom: Voices from the field - Dianawati, Heffy; Mulyono, Herri (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
This article documents an English as a foreign language (EFL) classroom writing activity to promote students’ creativity. This classroom writing activity had two main objectives: to provide students with writing exercises that would promote practical use of written English language as a means of communication, and to facilitate students’ creativity in engaging with and solving problems in their social community. A real-world pedagogic writing task was developed to achieve these two objectives. The activity was carried out in a junior secondary school extracurricular program with 16 students from Years 7 and 8. Students’ perceptions of the writing activity were positive, and more importantly, their awareness of social issues in the community improved as students became engaged in meaningful communicative situations in their real social environment.